Efektifitas Kerjasama Penelitian Dalam Perencanaan Pembangunan Daerah di Kabupaten Lumajang - Naufal Agrasane; Itok Wicaksono (SS&H: Studies in Social Sciences and Humanities, 2024)
Regional development is a complex effort and requires synergy between various related parties, including local governments and cooperation partners. Cooperation partners in regional development planning have a very important role in achieving sustainable and effective development goals. In this context, the effectiveness of cooperation partners is the main key to ensuring that existing resources and potential can be utilized optimally. The importance of cooperation between local governments and cooperation partners lies not only in the financial aspect, but also involves the exchange of knowledge, technology, and experience. In this era of globalization, where development challenges are increasingly complex, the involvement of cooperation partners is a must to increase regional capacity and competitiveness. The effectiveness of cooperation partners is also very relevant to the participatory concept in regional development planning. By involving various parties, including the private sector, civil society, and academic institutions, development planning can be more holistic and able to respond to various needs and aspirations of the community. Research cooperation partners are institutions or individuals who work together in implementing research activities. This kind of collaboration can involve various sectors, including educational institutions, government, industry, and non-profit organizations. The research used Qualitative Data collection techniques Using Interviews, Observations and Documentation. The data sources in this study use primary and secondary data, namely the main data in this study that researchers obtained from the results of interviews and observations of the Lumajang district government. Then using secondary data, which is obtained from books, journals related to the research conducted by researchers